Practice Pattern Survey for Paediatric Asthma in Nepal (SPAN) - Ghimire, Amrit; Mukhopadhyay, Aniruddha; Gaur, Vaibhav; Gogtay, Jaideep (Nepalese Respiratory Journal, 2024)
Background: In Nepal, asthma is one of the most prevalent diseases affecting children and is a leading contributor to childhood morbidity. Objectives: We evaluated the current perceptions and experiences of pediatricians in Nepal regarding the diagnosis and management of pediatric asthma. Methods: A questionnaire-supported, observation-based, cross-sectional survey was conducted digitally among paediatricians from Nepal who routinely manage patients ≤12 years of age with asthma. A total of 121 paediatricians from different practice settings participated in the survey. Results: Of patients who visit paediatricians, 31.6% were under 5 years and 26.6% were between 5 and 12 years of age. 90.08% of paediatricians found an increasing trend in asthma cases in the last 5 years in Nepal. 64.46% of paediatricians agreed that dust and dust mites were the most common triggers. Diagnosis based solely on history and physical examination was used by 54.54% of paediatricians. 49.59% of paediatricians prioritized getting back to the normal routine as the criterion for achieving asthma control. 43% of paediatricians prescribed oral bronchodilators, 31.4% oral steroids, 54.5% only short-acting beta2-agonist (SABA), 66.1% combination of inhaled corticosteroids and long-acting beta2-agonist (ICS/LABA), 96.7% ICS/SABA, 46% only ICS, and 66.1% nebulization therapy to their patients with asthma. Nine out of 10 paediatricians agreed that an average of 34.01% of their patients were on add-on montelukast with inhalation therapy. Pressurized metered dose inhaler (pMDI) + spacer + facemask with bronchodilators was suggested by 63.63% of paediatricians to manage asthma attacks at home. The average adherence to inhalation therapy was 47.02%. During the first interaction, most paediatricians spent at least 15 minutes educating patients/parents about the disease and its treatment. 67.77% of paediatricians or their paramedics checked patients’ inhalation techniques on every visit. Most paediatricians considered tear-off pads about asthma (46.3%) and videos on asthma for patients (31.4%) as the best tools that can increase patient awareness of asthma and inhalation therapy. Conclusion: Only half of the participating paediatricians in Nepal follow the Global Initiative for Asthma (GINA) strategy reports to diagnose and manage their patients with asthma. pMDI + spacer with or without a face mask was the most preferred device. Patient education and awareness were critical, and most paediatricians educated their patients regularly.